Design and development of fiber optic gyroscopes - Udd, Eric; Digonnet, Michel J. F. (SPIE Press, 2019)
"Realizing the potential of the fiber optic gyro, like the ring laser gyro, has been a long and expensive process. Many researchers have made important enabling contributions, and many more engineers have worked diligently for many years on solving the problems associated with realizing viable inertial navigation and guidance produce at affordable costs. This book arose from efforts to form a special session to commemorate the fortieth anniversary of the first hardware demonstration of the fiber gyro in 1976 by Vali and Shorthill. The chapters contain contributions from key engineers and scientists who have worked from as early as 1977 to the present on manufacturing high-performance fiber gyros for many applications"--